Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.


Let $\mathcal{F}(X,Y)$ be the set of all functions $f:X\longrightarrow Y$, and let $x_0 \in X$. Given: $$\Phi :\,\mathcal{F}(X,Y)\longrightarrow Y$$ Defined by $\Phi (f)=f(x_0)$ for $f\in\mathcal{F}(X,Y)$.


  1. The function f is injective if $f(x)=f(y)$ implies $x=y$ for all $x,y\in Dom(f)$
  2. The function f is surjective if for every $b\in Codom(f)$ there exists some $a\in A$ such that $f(a)=b$
  3. The function f is bijective if it is both injective and surjective


Is $\Phi$ surjective, injective, bijective?

My Solution

  1. $\Phi$ is surjective

    Proof: let $y\in Y$. We will show that there exists some element $x\in X$ such that $\Phi(f)=f(x)=b$. Define $f(x)=y, \forall x\in X$, We know $f\in\mathcal{F}(X,Y)$, because $\mathcal{F}(X,Y)$ is the set of all functions from $X$ to $Y$ therefore $\Phi(f)=f(x_0)=y$, thus $\Phi$ is Surjective $\hspace{15cm}$ ${\Large ▫}$

  2. $\Phi$ is not injective:

    Proof: Special case If $|X|=1$, then $\Phi$ is injective.

    But when $|X|>1$, $\Phi$ is not injective. Ok here I get stuck. I cant figure out how to define two functions such that $\Phi$ isn't injective.

My Question

  1. Is the surjective proof correct?
  2. How can I define two functions in $\mathcal{F}$ such that $\Phi$ is not injective?

Can someone give me some hints/tips?

share|cite|improve this question

1 Answer 1

up vote 3 down vote accepted

Your surjectivity proof is ok.

You observe that $\Phi$ is injective if $|X|=1$. Note that $\Phi$ is also injective if $Y=\emptyset$ or $|Y|=1$. (You should prove injectivity in these three cases)

If $x_1\in X$ and $y_0, y_1\in Y$ with $x_1\ne x_0$, $y_0\ne y_1$, you can define two functions $f,g\colon X\longrightarrow Y$, namely $f(x)=y_0$ and $$g(x)=\begin{cases}y_0&\text{if }x=x_0,\\y_1&\text{otherwise.}\end{cases}$$ Then $\Phi(f)=\Phi(g)=y_0$, but $f\ne g$ because $f(x_1)=y_0\ne y_1=g(x_1)$.

share|cite|improve this answer
Great, I get it now! Thank you –  Onur Oct 22 '12 at 22:05

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.